Pressure-induced decomposition of β-SnWO4 - Sergio Ferrari; Daniel Diaz-Anichtchenko; Pablo Botella; Jordi Ibáñez; Robert Oliva; Alexei Kuzmin; Alfonso Muñoz; Frederico Alabarse; Daniel Errandonea (Results in Physics)
This study reports the decomposition of β-SnWO4 into Sn, SnO2, and WO3 induced by static compression. We performed high-pressure synchrotron powder angle-dispersive X-ray diffraction measurements and found that decomposition occurs at a pressure of 13.97(5) GPa and is irreversible. This result contradicts a previous study that, based on density-functional theory calculations and crystal-chemistry arguments, predicted a pressure-driven transition from β-SnWO4 to α-SnWO4. Our analysis indicates that the observed decomposition is unrelated to mechanical or dynamic instabilities. Instead, it likely stems from frustration of the β → α transition, as this transformation requires a change in Sn coordination from octahedral to tetrahedral.The assessment of how pressure influences the volume of the unit cell provided an accurate determination of the room-temperature pressure–volume equation of state for β-SnWO4. Furthermore, the elastic constants and moduli, as well as the pressure dependence of Raman and infrared modes of β-SnWO4, were derived from density-functional theory calculations. Several phonon modes exhibited softening, and three cases of phonon anti-crossing were observed.